2021
DOI: 10.1155/2021/8154810
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Melioidosis: A Single-Centre, 10-Year Retrospective Cohort Study

Abstract: Melioidosis is a tropical infectious disease with diverse clinical presentations. We aimed to investigate the characteristics and mortality risk factors of patients diagnosed with melioidosis in the past 10 years. This was a retrospective cohort study conducted at a quaternary care centre in South India. Clinical, demographic, and biochemical data in patients diagnosed with melioidosis with cultures were collected between January 2011 and December 2020 from medical records. Logistic regression analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Few centers in India have the expertise to identify and diagnose cases of melioidosis. These centers are located in the coastal states in south India such as Karnataka, Kerala, and Tamil Nadu with adjoining union territory Puducherry and Odisha in eastern India [8,10,[12][13][14]. However, it is now increasingly being recognized in other regions of the country including northern, north-western India [15,16], and now central India.…”
Section: Discussionmentioning
confidence: 99%
“…Few centers in India have the expertise to identify and diagnose cases of melioidosis. These centers are located in the coastal states in south India such as Karnataka, Kerala, and Tamil Nadu with adjoining union territory Puducherry and Odisha in eastern India [8,10,[12][13][14]. However, it is now increasingly being recognized in other regions of the country including northern, north-western India [15,16], and now central India.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic renal failure usually have defective granulocyte, and the T-cell function has a lower immunity, which predisposes to melioidosis with or without other infections. [ 17 ] The multimodal approach for primary prevention and glycaemic treatment of type 2 diabetes would possibly reduce the overall problem of melioidosis more effectively than any of the above five strategies for neglected tropical diseases (NTD) prevention. Heavy alcoholics are also prone to getting the infection of Burkholderia.…”
Section: Current Gaps In Diagnosis and Preventionmentioning
confidence: 99%
“…A systematic review from India for the period 1991-2018 found diabetes mellitus to be a major predisposing condition in 70% of reported cases [16]. There are multiple reports of melioidosis from various parts of India [15,16,[23][24][25], but it is not a notifiable disease. Estimates suggest that melioidosis is endemic to India with an annual burden of ~52,006 cases and death count of 31,425 (13,405-75,601) cases, with further escalation of the mortality rate to 90% if the disease remains undiagnosed and untreated [10].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Host factors such as the presence of one or more preexisting conditions that alter immune response (such as long standing uncontrolled diabetes mellitus or chronic renal failure), severe or penetrating injury or near-drowning are favorable for the occurrence of melioidosis [8,12,13]. In India, cases of melioidosis have been recognized from different regions, however case identification is confined to few tertiary centres due to limited diagnostic facilities [14][15][16]. The incidence of melioidosis in India is unknown but could be substantial due to the high burden of diabetes mellitus [17] and long coastline prone to extreme weather conditions.…”
Section: Introductionmentioning
confidence: 99%